Efficiency of different BFRP-based strengthening techniques in improving flexural behavior of RC slabs. (15th November 2021) - He, Weidong; Wang, Xin; Ding, Lining; Wu, Zhishen
Highlights: BFRP sheet, BFRP bar, and BFRP grids are used as strengthening materials. Externally bonded (EB), near-surface mounted (NSM), and composite reinforced mortar (CRM) strengthening techniques are compared. Failure mode is sensitive to strengthening technique. Prestressed BFRP grids are attempted for further improving serviceability. Abstract: This study aims to analyze the flexural behavior of one-way reinforced concrete (RC) slabs strengthened with basalt fiber-reinforced polymers (BFRP). A total of six slabs were constructed and subjected to four-point flexural experimental tests. One slab served as the control specimen, and two slabs were strengthened with externally bonded (EB) BFRP sheets and near-surface mounted (NSM) BFRP bars, respectively. The other three slabs were strengthened with a composite reinforced mortar (CRM) layer composed of BFRP grids and polymer cement mortar, of which the BFRP grids for one slab were nonprestressed, and those for the remaining two slabs were prestressed. The experimental results indicated that the types of strengthening techniques including EB, NSM and CRM affected the failure mode of the strengthened slab. In comparison with the EB and NSM techniques, the CRM technique was more efficient in improving the serviceability and ultimate behavior of RC slabs, and it was considerably more economical. Meanwhile, the application of prestress in the CRM technique could further improve the cracking load and flexural stiffness of the strengthened slabs. Additionally, an analytical model was presented to predict the cracking and yield loads of the strengthened slabs, and the predictions showed a good agreement with the experimental results.